Leiomiossarcoma mixoide de vagina: relato de caso - Alexandre, Camila Flávia Uchôa (2021)
Primary malignant lesions of the vagina are uncommon and vaginal sarcomas are even more rare. leiomyosarcomas are tumors that originate from smooth muscle. We describe a rare case of myxoid leiomyosarcoma of the vagina with initial proposal a surgical treatment. A 31-year-old woman, with an active sex life, presented a vaginal mass, whose histopathological examination revealed myxoid leiomyosarcoma in the vagina, requiring a complementary immunohistochemical study that confirmed the diagnosis. The patient underwent surgery for excision of the lesion, with good results. The patient remains in follow-up at the oncology surgery outpatient clinic, and has no disease recurrence. Experience with vaginal leiomyosarcomas is limited. Optimal treatment methods have not yet been established due to the rarity of the tumor